ANALISIS KINERJA KEUANGAN PERUSAHAAN ASURANSI DI INDONESIA SEBELUM DAN SESUDAH ADANYA UNDANG-UNDANG BADAN PENYELENGGARA JAMINAN SOSIAL - Muhammad Farham Madina (Fakultas Ekonomi Universitas 45 Surabaya, 2017)
Since the enactment of the Laws of the Social Security Agency (UU BPJS) on October 28, 2011 and the national social security system legislation beginning January 1, 2014, the Government of the Republic of Indonesia requires every Indonesian citizen to be registered in the national social security system under the auspices of the Social Security agency (BPJS), aims to raise the standard of living by providing social security at affordable or cheap prices to all Indonesians. This study using event study method, which aims to determine whether there are changes in the financial performance using underwriting ratio, solvency margin ratio, and likuidity asset ratio at an insurance company in Indonesia before and after the issuance of government policy that requires all citizens to follow the national social security. The sample used is 14 health insurance companies operating in Indonesia, with a range of one year before and one year after the event. The data used are secondary data, which then conducted different test using Paired Sample T-Test to know whether there is difference of Underwriting ratio, solvency margin ratio, and liquidity asset ratio. Based on the result of Paired Sample T-Test statistic test, there is no difference of Underwriting ratio, solvency margin ratio, and liquidity asset ratio in one year before and one year after government event or policy requiring every citizen to follow national social security.